Pengembangan Daerah Pariwisata melalui Pemanfaatan Upacara Adat Rambu Solo Kabupaten Toraja Utara - Uras Siahaan; Margareta M. Sudarwani; James Rilatupa (JURNAL ComunitÃ Servizio : Jurnal Terkait Kegiatan Pengabdian kepada Masyarakat, terkhusus bidang Teknologi, Kewirausahaan dan Sosial Kemasyarakatan, 2020)
Burial ceremonies have become very important icons for tourism in Toraja, especially North Toraja. All the attention of the population, including the North Toraja Regional Government will be focused on this ritual activity. Houses (Tongkonan) and Lumbung Padi (Alang) buildings are maintained and maintained to carry out the ceremony, so that the existence of these traditional houses is maintained. In research on the preservation of the burial ceremony building, the principles of conservation and revitalization of the ceremonial building have been conveyed. In Community Service Activities, the PPM team of the UK PPs Masters of Architecture Study Program has conducted several counseling on issues of conservation and revitalization of the Funeral Complex. The funeral ceremony tradition also has a negative impact on the use of vast land, the problem of environmental preservation and unlimited use of bamboo material, which should be preserved and cultivated. In addition, building maintenance techniques and the use of other materials that are more sustainable will be one way to preserve and cultivate bamboo plants. With the development of building techniques and funeral implementation systems, this tradition will continue to be preserved and the cost of the funeral can be an alternative to saving the cost of the funeral Keywords: . Funeral Ceremony, Building preservation,Rambu Solo